The Effect of Two Root Canal Sealers on the Retention of Glass Fibre Endodontic Posts - O'Connell, Brian; Davis, Siobhan (My University, 2007)
This study was undertaken to examine the effect of eugenol-containing and non-eugenol-containing root canal sealers on the retention strength of glass fibre endodontic posts (ParaPost Fibre White) luted with a resin cement (ParaPost cement). We also examined the mode of failure that occurred visually by using scanning electron microscopy. Seventy-two single rooted, recently extracted, premolar teeth were root canal treated and randomly divided into two groups. Group 1 was obturated with gutta percha and a calcium hydroxide-based sealer (Sealapex, Kerr). Group 2 was obturated with gutta percha and a eugenol-based sealer (Tubli-Seal Kerr). The teeth were stored for 1 week in distilled water at 37 degrees C and then prepared for 9 mm posts with a 1.40-mm drill. The matching glass fibre post was luted with a resin cement following the manufacturer's instructions. The samples were stored for 1 week and thermocycled. The posts were removed from the root canals using a calibrated testing machine in tensile mode. The mean dislodging force for group 1 was 190.46 N and for group 2 was 183.8 N, with standard deviations of 54.9 and 56.0 N respectively. The t-test indicated no significant difference between the two groups. Failure of the posts occurred mainly within the resin layer. This study showed that under experimental conditions there was no statistically significant difference between Sealapex sealer and Tubli-Seal sealer on the retention of glass fibre posts using a resin cement.
PUBLISHED
Keywords: Endodontics; Resin cement; Eugenol; Glass fibre; Endodontic post–dentine bonding